Four Cases of Hemangiopericytoma and the Contribution of Radiotherapy in Their Management - Ilangovan, Bhargavi; Sasikumar, Neetu; Stumpf, Janos; Devi, Rathna; Venkatraman, Murli; Kalyanaraman, S.; Chendhilnathan (Indian Journal of Neurosurgery, 2017)
Hemangiopericytomas are tumors arising from the Zimmerman pericytes. They are characterized by their propensity to recur aggressively and metastasize. Surgery forms the primary treatment modality. Radiotherapy has been used in the postoperative setting and has proved to produce a significant progression-free survival in cases with residual disease. Radiotherapy has been applied even as a single modality treatment whenever surgery could not be performed. We are presenting four cases of meningeal hemangiopericytomas which have been treated with radiotherapy in combination with surgery. These cases show various scenarios in which Radiotherapy has been used in hemangiopericytoma: adjuvant setting, residual/recurrent setting, and in the palliative setting. As far as the technique is concerned, three-dimensional conformal radiotherapy, fractionated radiosurgery, and other forms of high-precision irradiation (intensity-modulated radiation therapy [IMRT]) were given.
Keywords: hemangiopericytoma; radiotherapy; radiosurgery